Answer:
x=2, y=-7
Step-by-step explanation:
Given the system of equations:
![\begin{gathered} x+y=-5 \\ x-y=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s9slncmh7ygvpc8yk4oncxtltz9ysnl6ta.png)
To solve the system by elimination, we add the two equations to eliminate y.
![\begin{gathered} (x+x)+(y-y)=-5+9 \\ 2x=4 \\ x=(4)/(2) \\ x=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5c23k5koymyw751muc3vl5ccj16krbdvsq.png)
Next, we substitute x=2 in any of the equations to solve for y.
![\begin{gathered} x-y=9 \\ 2-y=9 \\ y=2-9 \\ y=-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mq0gdjdjg1tt9zvm4jl5tfqak0u8532uic.png)
The solution to the system of equations is therefore: (2, -7).